2021
DOI: 10.3390/bioengineering9010002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Macrophage and Cytokine Interactions with Biomaterials Used in Negative-Pressure Wound Therapy

Abstract: Macrophages are innate immune cells that help wounds heal. Here, we study the potential immunomodulatory effects of negative-pressure wound therapy (NPWT) materials on the macrophage inflammatory response. We compared the effects of two materials, Granufoam™ (GF) and Veraflo Cleanse™ (VC), on macrophage function in vitro. We find that both materials cause reduced expression of inflammatory genes, such as TNF and IL1B, in human macrophages stimulated with bacterial lipopolysaccharide (LPS) and interferon-gamma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…We observed increased cell spreading on Col-AA compared to that in Col-HEP-conjugated surfaces, likely due to enhanced integrin-mediated focal adhesion (Figure C). These findings were in line with earlier observations wherein the focal adhesion protein vinculin was found to stabilize adhesion receptors, promote cell spreading, and transmit force at cell–cell and cell–matrix junctions. , In addition, macrophage adhesion to its substrate is an important determinant of its inflammatory activation as our work has shown that short durations of adhesion or adhesion to ultralow binding surfaces significantly suppresses inflammatory activation. , Increased cell spreading in Col-AA may have caused enhanced adhesion and translocation of YAP/TAZ into the nucleus, resulting in higher secretion of inflammatory cytokines. In addition, the fibrillar structure of Col-HEP-conjugated surfaces may discourage optimal cell–matrix adhesion and cell spreading, likely due to limited interactions with focal adhesions while promoting engagement of inhibitory receptor LAIR-1 with its ligands in the collagen; together, these effects could lead to suppressed inflammatory activation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed increased cell spreading on Col-AA compared to that in Col-HEP-conjugated surfaces, likely due to enhanced integrin-mediated focal adhesion (Figure C). These findings were in line with earlier observations wherein the focal adhesion protein vinculin was found to stabilize adhesion receptors, promote cell spreading, and transmit force at cell–cell and cell–matrix junctions. , In addition, macrophage adhesion to its substrate is an important determinant of its inflammatory activation as our work has shown that short durations of adhesion or adhesion to ultralow binding surfaces significantly suppresses inflammatory activation. , Increased cell spreading in Col-AA may have caused enhanced adhesion and translocation of YAP/TAZ into the nucleus, resulting in higher secretion of inflammatory cytokines. In addition, the fibrillar structure of Col-HEP-conjugated surfaces may discourage optimal cell–matrix adhesion and cell spreading, likely due to limited interactions with focal adhesions while promoting engagement of inhibitory receptor LAIR-1 with its ligands in the collagen; together, these effects could lead to suppressed inflammatory activation.…”
Section: Discussionsupporting
confidence: 92%
“… 52 , 53 In addition, macrophage adhesion to its substrate is an important determinant of its inflammatory activation as our work has shown that short durations of adhesion or adhesion to ultralow binding surfaces significantly suppresses inflammatory activation. 17 , 54 Increased cell spreading in Col-AA may have caused enhanced adhesion and translocation of YAP/TAZ into the nucleus, resulting in higher secretion of inflammatory cytokines. In addition, the fibrillar structure of Col-HEP-conjugated surfaces may discourage optimal cell–matrix adhesion and cell spreading, likely due to limited interactions with focal adhesions while promoting engagement of inhibitory receptor LAIR-1 with its ligands in the collagen; together, these effects could lead to suppressed inflammatory activation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that Mreg/anti-inflammatory macrophages exhibit elongated morphology and cells express M2 phenotype markers even in the absence of exogenous stimuli [ 11 , 30 ]. Therefore, we first examined the cell morphology and the degree of cell elongation by microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Thanks to the recent progress registered in the fields of materials science and TE, it is possible to modulate the physicochemical and biological properties to generate a biobased scaffold for various applications, from antibacterial surfaces [60] and engineered bacteria [61] to tissue regeneration [62][63][64][65][66] and wound healing [17,67,68]. Particularly, cellbiomaterial interactions are crucial to determine the cellular fate in terms of adhesion [69,70], proliferation [71], differentiation [72,73], morphology [74,75], migration [76,77], and for the ECM-mimetic scaffold fabrication [78,79].…”
Section: Modulation Of Cell Fate By Cell-biomaterials Interactionsmentioning
confidence: 99%